1 0 0 0 n = 0 ∑ ∞ 6 n σ 0 ( 6 n )
Find the value of the expression above if σ 0 ( x ) is the number of factors of x . It is also called the divisor function.
As an explicit example, 4 has 3 factors 1,2 and 4, so σ 0 ( 4 ) = 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I was surprised that the answer was 2016.
BTW, you can simplify the sum as
n = 0 ∑ ∞ 6 n ( n + 1 ) 2 = 6 n = 1 ∑ ∞ 6 n n 2
Log in to reply
Wonderful problem in which 2016 comes again!
Level 5? How?
To be honest I only have a few Lvl 5 questions so I am happy.
When you differentiate x n wouldn't it be n . x n − 1 ?
Log in to reply
Yes. This was from an earlier question. We took the derivative then multiplied by x
Differentiation=not required
Problem Loading...
Note Loading...
Set Loading...
You might want to see this first
∑ n = 0 ∞ 6 n σ 0 ( 6 n ) = ∑ n = 0 ∞ 6 n σ 0 ( 2 n × 3 n ) = ∑ n = 0 ∞ 6 n ( n + 1 ) ( n + 1 ) s i n c e 2 a n d 3 a r e p r i m e . = ∑ n = 0 ∞ 6 n ( n + 1 ) 2
n = 0 ∑ ∞ x n = 1 − x 1 ∀ ∣ x ∣ ≤ 1
⇒ n = 0 ∑ ∞ ( d x d x n ) = d x d ( 1 − x 1 ) ⇒ n = 0 ∑ ∞ ( n ⋅ x n ) = ( 1 − x ) 2 x ⇒ n = 0 ∑ ∞ d x d ( n ⋅ x n ) = d x d ( ( 1 − x ) 2 x ) ⇒ n = 0 ∑ ∞ ( n 2 ⋅ x n ) = x ⋅ ( 1 − x ) 4 ( 1 − x ) 2 + 2 x ⋅ ( 1 − x ) = ( 1 − x ) 3 x + x 2
so now we have
∑ n = 0 ∞ 6 n 1 = 1 − 6 1 1 = 5 6
∑ n = 0 ∞ 6 n n = ( 1 − 6 1 ) 2 6 1 = 2 5 6
∑ n = 0 ∞ 6 n n 2 = ( 1 − 6 1 ) 3 6 1 + ( 6 1 ) 2 = 1 2 5 4 2
∑ n = 0 ∞ 6 n ( n + 1 ) 2 = ∑ n = 0 ∞ 6 n n 2 + 2 n + 1 = ∑ n = 0 ∞ 6 n n 2 + 2 ∑ n = 0 ∞ 6 n n + ∑ n = 0 ∞ 6 n 1 = 1 2 5 4 2 + 2 × 2 5 6 + 5 6 = 1 2 5 2 5 2
OR
∑ n = 0 ∞ 6 n ( n + 1 ) 2 = ∑ n = 1 ∞ 6 n − 1 n 2 = 6 ∑ n = 1 ∞ 6 n n 2 = 6 ( ∑ n = 0 ∞ 6 n n 2 − 0 ) = 6 × 1 2 5 4 2 = 1 2 5 2 5 2
1 2 5 2 5 2 × 1 0 0 0 = 2 0 1 6
The middle part was from one of solutions from my first question.